Enhanced antiviral immunity against Bombyx mori cytoplasmic polyhedrosis virus via overexpression of peptidoglycan recognition protein S2 in transgenic silkworms. (October 2018) - Zhao, Ping; Xia, Fei; Jiang, Liang; Guo, Huizhen; Xu, Guowen; Sun, Qiang; Wang, Bingbing; Wang, Yumei; Lu, Zhongyan; Xia, Qingyou
Abstract: In insect innate immunity, peptidoglycan recognition proteins act as pattern recognition receptors, helping hosts combat invasive microorganisms. Bombyx mori cytoplasmic polyhedrosis virus (BmCPV) is the main silkworm pathogen that invades the midgut columnar cell layer. We previously reported that B. mori peptidoglycan recognition protein S2 (BmPGRP-S2) was upregulated in silkworm larvae after BmCPV infection. Here, we constructed a transgenic vector overexpressing BmPGRP-S2 under the control of a midgut-specific promoter. Transgenic silkworm lines (PGRPS2-1 and PGRPS2-2) were generated via embryonic microinjection. BmPGRP-S2 was successfully overexpressed in transgenic silkworms and BmE cells. After oral inoculation with BmCPV, the mortality of PGRPS2-1 and PGRPS2-2 decreased by approximately 36% and 32%, respectively, compared with that of the non-transgenic line, and BmCPV mRNA contents were significantly lower. In the PGRPS2-1 line, imd, relish, and the antimicrobial peptide (AMP) genes attacin2, gloverin2, and moricin showed increased expression after viral infection; however, the Toll pathway was not activated. These results indicate that BmPGRP-S2 overexpression can activate the Imd pathway and induce AMP upregulation, enhancing silkworm antiviral resistance. Highlights: Bombyx mori cytoplasmic polyhedrosis virus (BmCPV) is a major silkworm pathogen. BmCPV infection increases peptidoglycan recognition protein S2 (BmPGRP-S2) levels. High BmPGRP-S2 induces Imd pathway component and antimicrobial peptide expression. Transgenic lines with high BmPGRP-S2 were more resistant, with lower mortality.